ANALYSIS OF ENERGY EFFICIENT SOLUTIONS OF A SMALL CAPACITY ELECTRIC ARC FURNACE AND THEIR SYNTHESIS IN A NEW GENERATION 15-TON UNIT (Modern Problems of Metallurgy, 2020)
On the basis of mathematical modeling and numerical experiment were analyzed the factors to increase energy efficiency of the electric arc furnace (EAF) of a small capacity. Optimization of depth of the steelmaking bath is performed, which in combination with the bath blowing by an inert gas provides lowering of radiation heat loss by 21%; enhances heat- and mass transfer by 11-16%, heating and homogenization of liquid steel by 8%. Implementation of energy saving water-cooled panels and a system of dispersed aspiration reduce heat loss and fugitive emissions. The synthesis of innovative solutions in 15-t EAF will reduce total energy consumption by 3 - 5%.
Keywords: electric arc furnace, energy efficiency, geometry of the bath, energy-saving panels, dispersed aspiration system.